Candidíase vulvovaginal: sintomatologia, fatores de risco e colonização anal concomitante - Holanda, Antônio Arildo Reginaldo de (2007)
Post-menarche patients with clinical signs of vulvovaginitis were analyzed in this study, whose aims were the following: identify the frequency of C. albicans and non C. albicans species and negative results, correlate the vaginal culture for yeast with risk factors and symptomatology; compare positive and negative results for yeast in the vaginal and anal cultures; compare the positive results for C. albicans with other results found in the vaginal and anal cultures; and compare concomitant positivity for C. albicans and non C. albicans in the vaginal and anal cultures. Sample selection occurred between May, 2003 and May, 2005, and included 99 patients from Natal, Brazil. The laboratory methods used consisted of CHROMagar Candida culture medium, thermotolerance test at 42-45°C and hypertonic NaCL, in addition to the classic methods of carbohydrate assimilation and fermentation. We used absolute numbers, percentages, means of central tendency, chi-squared test (χ2) with Yates correction, Fisher s exact test and odds ratio for statistical analysis. The most frequent species was C. albicans in 69% of the cases. The positivity for Candida spp showed an association with the use of tight-fitting intimate clothing and/or synthetics, allergic diseases and the occurrence of itching, leukorrhea and erythema. Anal colonization increased the likelihood of vaginal contamination by 2.8 and 4.9 times, respectively, for Candida spp and C. albicans. When compared to the other species, C. albicans-positive anal colonization increased by 3.7 times the likelihood of vaginal positivity. These data suggest likely vaginal contamination originating in the anus